Survey to define informational needs of patients undergoing surgery for Crohn's anal fistula. (4th December 2020) - Lee, Matthew J.; Jones, Georgina L.; Lobo, Alan J.; Brown, Steven R.; ,
Abstract: Aim: There are many surgical treatments used in Crohn's anal fistula, although none is perfect. Decisions about surgery in this condition may be preference sensitive. The aim of this study was to identify what information patients would like in order to make treatment decisions and to explore experiences of making decisions in this setting. Method: A survey was designed based upon qualitative interviews and input from patients and clinicians. It included a long list of informational items to be ranked on a scale of importance, a control preference scale, the decision regret scale, and items exploring preferred information formats. This was distributed through 10 English hospitals to patients with recent surgical treatment for Crohn's anal fistula. Results were analysed using principal component analysis, to identify key informational needs, and other appropriate descriptive statistics. Results: In total 92 questionnaires were returned (response rate 41.8%); 48 (52.5%) respondents were women and 54 (58.7%) had undergone seton insertion. Principal component analysis identified three information needs: wound and aftercare, effect on perianal symptoms, severity of surgery. Decision‐making preferences showed a desire to participate in decision‐making. Median decision regret score was 25/100 (i.e., low). The preferred format for sharing information to support decision‐making was from the surgeon, 80/92 (87.0%), and from a booklet, 58/92 (63.0%). Conclusion: Key informational needs in this condition are wound and after care, effect on perianal symptoms, and severity of surgery. Patients would like this information to help engage in shared decision‐making.